Eight weeks of plyometric training improved the change of direction abilities of adolescent basketball players - Yang, C. (International Journal of Sports Science and Coaching, 2025)
The effectiveness of plyometric training in adolescent basketball players has not been fully elaborated, especially its effect on enhancing change of direction abilities. Thirty male adolescent basketball players were divided into plyometric and resistance training groups for an 8-week training period. The improvement in change of direction abilities before and after the training was assessed using the Lane Agility Drill test. Motion capture system, force platforms, and electromyography were utilized to investigate the characteristics of lower limb kinematic and kinetic features before and after training. At post-test, the Lane Agility Drill finish time for the plyometric group was significantly less than that of the resistance training group (P < 0.05, Cohen's d = 0.551), and the post-test Lane Agility Drill finish time for the plyometric group was significantly less than their pre-test time (P < 0.05, Cohen's d = 0.746). At post-test, the plyometric training group showed greater increases in peak impulse (P < 0.05, Cohen's d = 0.464), peak power (P < 0.05, Cohen's d = 0.684) compared to resistance training group. The study's conclusion indicates that compared to resistance training, plyometric training more significantly enhances athletes` change of direction abilities. This improvement is attributed to the superior transfer of strength and explosive power gains acquired during training. Additionally, plyometric training optimizes energy utilization and production during jumping and running.